Utility of rapid diagnostic kit tests for diagnosis of suspected dengue fever - Otta, Sarita; Swain, Bichitrananda (International Journal of Research in Medical Sciences, 2019)
Background: Dengue fever often presents as an undifferentiated febrile illness requiring a laboratory test for identification. Serological tests particularly on rapid kits for the detection of NS1Antigen, IgG and IgM antibodies are the most commonly performed test across the country. Methods: The serum samples of suspected dengue cases were tested by Rapid test kits for assessing all the three parameters as well as by ELISA for NS1 antigen test. The platelet count of the patients was obtained from automated coulter counter. The results thus obtained were analyzed in Excel format. Results: The serum samples from 304 suspected Dengue fever cases were received in the lab, of which 190 samples were positive either by rapid or ELISA and 176 when rapid card test was considered alone Highest seropositivity of dengue cases were observed in the age group of ≥60 years (79.2%) followed by 45-59 years (70.7%). On rapid test, 78 cases were NS1 antigen positive of which 60 cases were positive only for NS1 antigen. When NS1 rapid and ELISA tests when compared, 16 kit negative tests were positive on ELISA while 34 kit positive tests were ELISA negative. Sensitivity, specificity, PPV and NPV when only NS1 was considered on rapid test kits when compared with ELISA were 78.9%, 87.8%, 63.8% and 93.8%. 33.5% of serologically positive cases of Dengue had low platelet count on admission while only among negative cases 17.2% had a low platelet. Conclusions: Rapid kits often show variable results thus needing a validation of them from end user. As a positive dengue test result is an essential prerequisite for diagnosis thus it is essential that for serological tests ELISA technique should be used for reporting. Thus, it also mandates more efforts at decentralization of NVBDCP to include both government and non government institutions.